Peningkatan Hasil Belajar Matematika tentang Nilai dan Kesetraan Pecahan Mata Uang Melalui Media Video Pembelajaran Pada Siswa Sekolah Dasar - Mutik Ati Masrifatun (Universitas Sebelas Maret, 2020)
This research is an effort to improve Mathematics learning outcomes about the value and equivalence of currency fractions in grade II SD Negeri Dukun 1. Classroom action research was carried out through 2 cycles, namely cycle I and cycle II. Each cycle contains planning, implementation, observation and reflection. The data collection methods used include observation, tests, and documentation. Data analysis was carried out by calculating the achievement of the learning outcomes in each cycle marked by an increase in Classical Completeness Criteria.The results obtained in this study were that there was an increase in student learning outcomes for Mathematics about the value and equivalence of currency denominations in class II SD Negeri Dukun 1 students. students who complete learning, in cycle I increased to 50%, increased in cycle II to 90% of students completed. Based on these learning outcomes, it can be concluded that through the media of instructional videos it can improve Mathematics learning outcomes about the value and equivalence of currency fractions in grade II SD Negeri Dukun 1 st.